TEACHERS ROLE IN BUILDING VISUAL-IMPAIRMENT STUDENTS’ CONFIDENCE (A Case Study of Education Pattern in SLB-A’Aisyiyah Ponorogo). - Wiwik Fiana; Hadi Cahyono; Prihma Sinta Utami (EDUPEDIA, 2017)
This research aims to: 1) know teacher’ role in building visual-impairment students’ confidence; 2) know how positive are the impacts felt by students on teacher’s role in building visual-impairment students’ confidence. Method the used was qualitative with intake data used data source in the form of 1) primary data 2) data of secondary and as for data collecting technique the used was 1) Observation 2) Interview 3) documentation. used Data analysis in the form of data discount, presentation of data, verification. Result of from this research that is 1) School provide teacher as according to requirement of student. Teacher comprehend how student character and condition seen student enthusiasm and talent. Teacher grow to feel self confidence at student as according to potency and character had by student. Teacher parked to student to always dare to 2) Affect which was felt by student. Student feel more self confidence and dare to. Student can fulfill its requirement did everyday activity self-supportingly. Student earn and berkominukasi  have interaction with environment around and student can develop owned potency.